Resilience characteristics of port nodes from the perspective of shipping network: Empirical evidence from China. (15th April 2023) - Qin, Yafeng; Guo, Jianke; Liang, Muxin; Feng, Tianqi
Abstract: Ports are both the start and end points of shipping, they are connected by shipping routes, thereby forming a port shipping network that connects global industries and supply chains. Each port node has specific functions within the network, while its capacity to resist interference differs from that of other ports; consequently, when encountering external shocks, ports are not affected equally. Therefore, this paper proposes the concept of port node resilience from the perspective of the shipping network. This is achieved by analyzing the literature on regional, urban, and network resilience. Thereafter, by fully considering the complexity of port nodes' linkages, as well as their attributes vis-à-vis the shipping network, a three-dimensional (structure, function, and location) econometric model of port-node resilience is constructed. By examining data from China's container ports for the years 2008 and 2018, this study analyzes port nodes' resilience characteristics and the differences in space. The results indicate that the studied port nodes' resilience index presents the characteristic of clustering. Further, the average resilience index increased from 0.25 (low) to 0.43 (medium). The differences in port nodes' regional resilience narrowed, while their absorption and transformation capacity improved when facing external interference. Highlights: This study presents a three-dimensional model of port node resilience. It comprises the dimensions of structure, function, and location. Data from China's ports for the years 2008 and 2018 are analyzed. The average resilience index increased from low to medium. This study advances research on resilience within the context of shipping networks.